A new framework for mitigating urban heat island effect from the perspective of network - Jieling Luo; Ling Zhu; Hui Fu (Ecological Indicators)
Urban blue-green space (BGS) has a cold island effect, but many studies only focus on the cooling efficiency and patch area, without considering the impact of the overall patch connectivity on surface urban heat island (SUHI) effect. In this study, from the perspective of an ecological network, a combined cooling pattern of “point (source) −line (cooling corridor) −surface (cooling range and important area)” was proposed. Firstly, morphological spatial pattern analysis (MSPA) and landscape connectivity index used to identify cold and heat sources with high diffusion potential. Then, circuit theory (CT) is used to organize the source areas to form cooling corridors. Finally, the threshold of corridor cooling distance and the important areas affecting network connectivity are analyzed. Taking Haikou as an example, the study identified 13 heat sources and 21 cold sources, extracted 74 cooling corridors, determined the threshold of cooling distance to be 1100 m, formed a cooling network pattern, and identified a total of 11.45 km2 of important areas affecting the network, including 4.71 km2 of key areas and 6.74 km2 of obstacle areas. This framework can provide a new idea for climate-resilient urban planning.